2019
DOI: 10.3390/ijerph16091598
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Epidemiological, Ergonomic, and Longitudinal Cohort Studies Examining the Links between Stair and Bathroom Falls and the Built Environment

Abstract: Stair and bathroom falls contribute to injuries among older adults. This review examined which features of stairs and bathrooms have been assessed in epidemiological, ergonomic, and national aging studies on falls or their risk factors. Epidemiological and ergonomic studies were eligible if published from 2006–2017, written in English, included older persons, and reported built environment measures. The data extracted included the following: study population and design, outcome measures, and stair and bathroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 106 publications
1
10
0
Order By: Relevance
“…They have more chances to fall on the floor. These results were consistent with the previous study that found the danger of toilet or bathroom was falling [4,10,11,12,13]. The muscle strength in the upper and lower limbs of the elderly was degenerating, visual impairment, physical weakness, motion and sensory function decreases affected their balance ability [13,14].…”
Section: Discussionsupporting
confidence: 92%
“…They have more chances to fall on the floor. These results were consistent with the previous study that found the danger of toilet or bathroom was falling [4,10,11,12,13]. The muscle strength in the upper and lower limbs of the elderly was degenerating, visual impairment, physical weakness, motion and sensory function decreases affected their balance ability [13,14].…”
Section: Discussionsupporting
confidence: 92%
“…The PtDAs included a self-assessment to determine if personal care needs could be met at the family’s home, a home safety assessment, and suggestions to discuss care needs with current care providers. 20 22 Statements for the values-clarification exercise were informed by public responses to media reports. The final PtDAs met all IPDAS criteria (qualifying criteria, criteria to minimize risk of bias).…”
Section: Resultsmentioning
confidence: 99%
“…Even if fall risk factors such as BMI, types of medication, disease and social frailty are adjusted, it was shown that climbing stairs should be an area of concern among older people. Stairs are an environment where the risk of falling is high [ 29 ]. However, almost no objective characteristics that can prevent falls have been identified [ 30 ].…”
Section: Discussionmentioning
confidence: 99%